Effect of Antiplatelet Activity of Aspirin on Chronic Kidney Disease - Saqib Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background and aim: Individual differences in the pharmacological responsiveness to aspirin are considerable. A higher likelihood of ischemic episodes is linked to aspirin’s inadequate antiplatelet actions. It has been hypothesized that chronic kidney disease (CKD) influences the pharmacologic reaction to antiplatelet drugs. The elevated chance of fatality and cardiovascular problems in CKD sufferers has already been found to be largely explained by high on-treatment platelets response (HTPR) to clopidogrel. This research aimed to examine at how aspirin affects blood clotting in CKD sufferers. Method: We performed cross-sectional research on 120 people in Medical center of Lahore taking aspirin regularly. The thromboxane production generated by AAI was used to gauge the pharmacologic reaction to aspirin. Result: Individuals with poor kidney functioning were more likely to experience HTPR to aspirin (48% vs. 23%; odds ratio, 3.17; 95% confidence interval [CI], 1.35-7.42; P = 0.007). When compared to individuals with healthy or mildly diminished kidney performance, those with mild or serious CKD had lower pharmacokinetic responsiveness to aspirin (91; interquartile ranged [IQR], 281 ng mL-1; differential in medians, 56; CI, 6-110 ng mL-1; P = 0.012). Remaining thromboxane production and glomerular filtration rate were both associated by bivariate Pearson correlation analysis (R = 0.312; R2 = 0.093; P = 0.001). Individuals with CKD were usually old age and being women. Women and aged were not significant predictors of the connection, according to multivariate linear regression analyses (R = 0.313; R2 = 0.081; P = 0.002 and P = 0.006) respectively. Conclusion: Aspirin pharmacological reaction is associated with kidney function. Individuals who have CKD are more likely to have aspirin’s antiplatelet action compromised. To evaluate the therapeutic significance of this data and look into the best antithrombotic strategy for CKD individuals, additional research is required. Keywords: Chronic kidney disease, platelets, treatment, aspirin, cardiovascular